Validity of jitter measures in non-quasi-periodic voices. Part I: Perceptual and computer performances in cycle pattern recognition. - DeJonckere, Philippe; Schoentgen, Jean; Giordano, Andrea; Fraj, Samia; Bocchi, Leonardo; Manfredi, Claudia (Logopedics Phoniatrics Vocology, 2011)
The limit of about 5% for reliable quantification of jitter in sustained vowels of dysphonic voices--a widely accepted guideline--deserves critical analysis. The present study pertains to the effect of experience and training on the perceptual (visual) capability of correctly identifying periods in (highly) perturbed signals, and to a comparison of the performance of several programs for voice analysis. Synthesized realistic vowels (/a:/) with exactly known jitter (2.7%--31.5%) are used as material. After selection and training, experienced raters demonstrate excellent agreement in correctly identifying periods up to high values of jitter put in. Perceptual rating outperforms all computer programs in accuracy. Most remain reliable up to 10% jitter; one of them correctly measures up to the highest level.